Abrasion behavior and functional properties of composite vitreous enamel coatings fabricated with the addition of 316L stainless steel flakes. Issue 16 (15th August 2022) - Russo, Francesca; Fontanari, Vigilio; Rossi, Stefano
Abstract: Vitreous enamels are a type of inorganic coating used to protect metals from corrosion and weathering. Their durability is mainly determined by the resistance of the surface to mechanical stresses and damages. It is therefore crucial to improve enamel's mechanical properties since the brittleness of the glassy matrix can lead to catastrophic failure of the coating. The purpose of this study is to investigate the possibility of improving the abrasion resistance of enamel coatings by adding 316L stainless-steel flakes, used as a second ductile toughening additive. The abrasion resistance of the coatings has been studied by using the P.E.I. abrasion test, coupled with Electrochemical Impedance Spectroscopy (EIS) measurements, and SEM observations. The abrasion mechanisms were investigated thoroughly, and the influence of the additive on the functional properties of the coating was taken under consideration. The stainless steel flakes proved useful in improving the coating's abrasion resistance without compromising other functional properties.